The global sport economy contemporary issues - Desbordes, Michel; Aymar, Pascal; Hautbois, Christopher (Routledge research in sport business and management, 2019)
"This book examines the global sports ecosystem through three of its central pillars: sport marketing, sports equipment manufacture and sales, and sport governance and organisation. By focusing on these three themes the book presents a nuanced and multi-faceted view of how the global sports economy works and what its main strategic challenges and opportunities are. Offering a balance between theory and practice, and adopting an international perspective with case studies and examples from the Americas, Europe and Asia, the book addresses key issues such as corporate social responsibility, the impact of culture on international sport business, innovation and entrepreneurship, and consumer behaviour. The Global Sport Economy is fascinating reading for students, researchers and practitioners with an interest in sport business and management, sport marketing, the sporting goods industry and distribution and sport governance"--